Tetraparesis as clinical correlate of subacute cervical flexion myelopathy - Fehre, Katharina S.; Weber, Marc-André; Hensel, Cornelia; Weidner, Norbert (The journal of spinal cord medicine, 2016)
Context: We report the case of a 20-year-old woman who underwent tracheal resection with postoperative chin-to-chest suture for 10 days, presenting with severe tetraparesis at our institution. Similar cases have been reported previously, however, not yet in the pathophysiological context of chronic cervical flexion myelopathy (Hirayama syndrome).Findings: Extensive myelopathy at cervical level is the consequence of the fixed cervical spine position due to chin-to-chest suture. Predominantly affected young individuals (age range from 20-25 years) without evidence of degenerated spine disease suggest a similar mechanism as described in Hirayama syndrome—displacement of the dura with consecutive compression of the spinal cord vasculature.Conclusions: Subacute flexion myelopathy represents a serious complication of operative/postoperative fixed cervical spine positions, warranting particular attention by respective surgeons.
Gesehen am 14.05.2020